Impact of Capital Structure and Growth on the Profitability of Nepalese Commercial Banks - Khatri, Davi (Nepalese Journal of Business, 2024)
This study examines the impact of capital structure and growth on the profitability of Nepalese commercial banks. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are debt to equity ratio, debt to asset ratio, asset growth, deposit growth, loan to deposit ratio and capital adequacy ratio. The study is based on secondary data of 12 commercial banks with 108 observations for the period from 2013/14 to 2021/22. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the impact of capital structure and growth on the profitability of Nepalese commercial banks. The study showed that debt to equity ratio has a negative effect on return on assets. It means that increase in debt-to-equity ratio leads to decrease in return on assets. Likewise, debt to asset ratio has a positive effect on return on equity and return on assets. It means that increase in debt to asset ratio leads to increase in return on equity and return on assets. In contrast, assets growth has a negative effect on return on equity and return on assets. It shows that higher the assets growth, lower would be the return on equity and return on assets. However, deposit growth has a negative effect on return on equity and return on assets. It indicates that increase in deposit growth leads to decrease in return on equity and return on assets. In addition, loan to deposit ratio has a negative effect on return on equity. It indicates that increase in loan to deposit ratio leads to decrease in return on equity. Further, this study showed that there is a positive impact of capital adequacy ratio and return on assets. It means that larger capital adequacy ratio, higher would be the return on assets.